Tropical Australia is a potential reservoir of non-tuberculous mycobacteria in cystic fibrosis. Issue 5 (11th May 2017) - Sherrard, Laura J.; Tay, George T.; Butler, Claire A.; Wood, Michelle E.; Yerkovich, Stephanie; Ramsay, Kay A.; Reid, David W.; Moore, Vanessa L.; Kidd, Timothy J.; Bell, Scott C.
Improved survival rates and increased treatment intensity of people with cystic fibrosis have been accompanied by a rising incidence of multi-antibiotic resistant and difficult-to-treat respiratory pathogens, including non-tuberculous mycobacteria (NTM) [1]. NTM epidemiology in cystic fibrosis varies globally, with a prevalence of >20% in some geographical locations [2]. In particular, there are concerns that active NTM disease from rapidly growing mycobacteria ( Mycobacterium abscessus complex) may be increasing and causing accelerated pulmonary decline [3, 4]. NTM are found naturally in ecological niches such as soil and water, and susceptible individuals may also acquire infection from potable water in their homes [5, 6]. Recent reports demonstrate person-to-person transmission [7, 8], which might occur via fomites and cough aerosols [8] and further emphasise the potential clinical importance of these organisms. Living in tropical Australia is associated with NTM acquisition, whilst long-term azithromycin is protective in CF http://ow.ly/FrJi309W8DK